Mulheres (in) submissas: a multiplicidade de perfis na obra de Lília Momplé - Almeida, Maria Aparecida Nascimento de (2022)
This thesis discusses the female existence in Africa from the alternative concepts of the Western Feminism, considered mostly inadequate to express the longings and fears of the African Continent women and refused by the writer Lília Momplé, author of the works that compose the analysis corpus, namely, Ninguém matou Suhura, Os Olhos da Cobra Verde (short stories) and Neighbours (novel), in which the female oppression is notorious by questions related to race, class and gender; beyond the impact of tradition, which matrilineal practices persist in the Northern Mozambique, in opposition to the patrilineal practices that remain in the South of the country. Thus, the “cultural geography” is essential to for probing the profiles of the (um)submissive women, protagonists and supporting characters in Lília Momplé’s work, from the libertarian projects of writing and experience, for the female voices and writings, fictional and real, claim for autonomy in which concerns the form and contentes of narratives, as well as require a perspective approach of woman that mirrors the experienced reality. That is why we evoke the afrocentricity as a “methodological orientation”; and the Africana Womanism as a theoretical paradigma, which is considered appropriatefor such discussions, to encourage a liberating práxis from the race, class and gender oppression, in line with the African culture, allowing top robe the multiplicity of female profiles and verify the path taken from submission to insubmission through the agency concept.